Food web reconstruction of Barmaky, the oldest post-LGM hunter-gatherer site in north-western Ukraine - Reiss, Lilian; Pasda, Kerstin; Mayr, Christoph; Ludwig, Patrick; Stiller, Laura; Chabai, Victor; Maier, Andreas (Boreas, 2025)
The site of Barmaky currently marks the oldest Epigravettian occupation of north-western Ukraine shortly after the Last Glacial Maximum (LGM), dated to around 19 cal. ka BP. Stable isotope analyses of bone collagen from six terrestrial mammals and two bird species show a comparatively highly structured palaeo-food web. Characteristic are high δ15N values in mammoth (Mammuthus primigenius) bone collagen compared with other herbivores and δ13C values showing niche partitioning between mammoth and hare on the one hand and reindeer on the other. These findings may indicate differentiated herbivore niches, with different diets and habitats between herbivorous groups. Additionally, different mobility patterns could cause isotopic scatter in food webs. To better understand the context of early post-LGM mammoth behaviour, we compare the mammoth δ15N values of Barmaky (19.0 cal. ka BP; 7.2±0.1‰) with those of Yudinovo (lower layer: 19.1/18.3–15.1 cal. ka BP and upper layer: 14.8–13.8 cal. ka BP; 7.3±1.0‰), Yeliseevichi (17.6 cal. ka BP; 5.7±0.8‰) and Mezhyrich (18.5–17.5 cal. ka BP; 4.3±0.8‰). At all sites, δ15N values of mammoths are comparatively high, except for Mezhyrich and a single specimen from Barmaky. In comparison with sedentary hares, mammoths from Barmaky suggest a non-locally dominated δ15N signal, while the mammoths from Mezhyrich show the local isotope signal. We also discuss the potential role of differences in temperature, precipitation and permafrost development for the different locations. Results from climate models indicate a gradient in temperature and precipitation with possible implications for food availability in the mammoth steppe.
CRIS-Team Scopus Importer:2025-07-04